Handbook of digital forensics of multimedia data and devices - Ho, Anthony T. S. 1958 (Wiley, 2015)
"Focuses on the interface between digital forensics and multimedia forensics, bringing two closely related fields of forensic expertise together to identify and understand the current state-of-the-art in digital forensic investigation"